2017
DOI: 10.12973/eurasia.2014.1204a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Self-Efficacy Scale of Technology Usage in Education

Abstract: The purpose of this study was to develop a scale instrument to allow us to establish the self-efficacies of elementary education teachers regarding their use of information technologies when educating their students. The study group comprised a total of 924 teachers from different branches working in central Ankara elementary schools. Based on the data acquired from the scales, exploratory and confirmatory factor analyses were conducted during the process of testing the construct validity of the scale. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Furthermore, not only the students will be happy with this recent development, research also shows that teachers on the other hand have a positive view of using interactive learning tools. The results observed in this research mirror those of the previous literatures (Dogru, 2014;Podschuweit, et.al 2016;Tanahoung et.al 2009) that examined the effect of introducing interactive learning environment at both secondary and tertiary institutions. One of the significant implications of this finding is that of improving students motivation towards learning and helping them to successfully pass their examinations with a high grades.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, not only the students will be happy with this recent development, research also shows that teachers on the other hand have a positive view of using interactive learning tools. The results observed in this research mirror those of the previous literatures (Dogru, 2014;Podschuweit, et.al 2016;Tanahoung et.al 2009) that examined the effect of introducing interactive learning environment at both secondary and tertiary institutions. One of the significant implications of this finding is that of improving students motivation towards learning and helping them to successfully pass their examinations with a high grades.…”
Section: Discussionsupporting
confidence: 87%
“…Lin and Hwang (2014) investigated the relationship between an individual's influence on innovation and technology adoption and found that self-efficacy and personal perceptions about the ability to create knowledge using I.T. has a direct influence on affective commitment (Doǧru, 2017;Jaradat et al, 2018). Studies on the relationship between self-efficacy and perceived ease of use are contradictory in their results.…”
Section: Self-efficacy and Technology Adoption Behaviormentioning
confidence: 99%
“…Hence, learners' appropriate attitudes and adequate selfefficacy toward the internet is the critical prerequisite for the internet-based instruction. Although internet self-efficacy scale was constructed and validated by other researchers also (Tsai 2004;Raja 2016;Dogru 2017) but the findings of the present study would provide new and additional internet self-efficacy scale for adolescents. So after a thorough scrutiny of the available literature and tools, the researchers felt the need to construct a scale that will probe deeper into the internet self-efficacy of adolescent students.…”
Section: Introductionmentioning
confidence: 83%